(untitled) (African Journal of Biomedical Research, 2020)
Glaucoma is a growing public health challenge and raised intraocular has been found to be the only modifiable risk factor. The aim of this study was to assess the effect of exercise on intraocular pressure. This was a prospective case control study in which twenty consecutive newly diagnosed primary open angle glaucoma patients (POAG) were included as cases while 20 age- matched normal subjects were controls. The intraocular pressure in both eyes at baseline and at various time intervals post exercise were measured with a Perkins hand held applanation tonometer and recorded for both cases and controls. The results were collated and analysed with the version 20 SPSS software. The intraocular pressure was observed to significantly decrease after exercise on the treadmill at various time intervals (p<0.05). This study suggests that exercise may reduce intraocular pressure in Nigerians. Larger studies are needed to better elucidate the effect of exercise on intraocular pressure in this population of Nigerian subjects.